Risk factors for supply chain management of fast container shipping [electronic resource] - Asmawi Ismail, 1972-; Mohd. Zamani Ahmad, supervisor; Fakulti Kejuruteraan Mekanikal (2009)
Thesis (Sarjana Kejuruteraan (Mekanikal - Teknologi Marin)) - Universiti Teknologi Malaysia, 2009